THE POWER OF IDIOMS AND EXPLORING COMMON EXPRESSIONS ACROSS ENGLISH AND UZBEK CULTURES (International Conference on Modern Science and Scientific Studies, 2025)
This study explores the linguistic and cultural significance of weather-related idioms in English and Uzbek. By analyzing a variety of idiomatic expressions tied to natural phenomena such as rain, sun, wind, and snow, the paper aims to identify the underlying cognitive and cultural concepts that shape these expressions in both languages. The research emphasizes the metaphorical use of nature in shaping worldviews and cultural identity. Through comparative analysis, this paper highlights both shared and divergent cultural values and linguistic patterns, offering a deeper understanding of the role of idioms in the everyday life and worldview of English and Uzbek speakers.